INTERRELIGIOUS DIALOGUE TODAY: OBSTACLES AND OPPORTUNITIES - Fitzgerald, Michael L. (Journal of Dharma, 1994)
In a document published two years ago, Dialogue and Proclamation, three paragraphs are give.n over to listing obstacles to dlaloque. There comes first a one-line observation: "Already ona purely human level it is not easy to practise dialogue." This may Sound banal. It is a simple fact of experience. If dialogue at the purely human level means "reciprocal communication, leading to a common goal or, at a deeper level, to interpersonal communion," it is only achieved with difficulty, even between married couples, in families or in religious communities. Qualities are required such as openness, acceptance, patience, honesty and unselfishness. If dialogue needs to be worked at, even when the partners are homogeneous, it will be readily understood that interreligious dialogue, supposing by definition a difference of religion, "is even more difficult."